Given:
f(x)=sin2x+cosxsinx−cos2x
Let u=sin2x+cosx
Then,
dudx=2sinxcosx−sinx
Let v=sinx−cos2x
Then,
dvdx=cosx−2cosx(−sinx)=cosx+2cosxsinx
Rearranging
dvdx=2sinxcosx+cosx
We have,
ddx(uv)=vdudx−udvdxv2
Substituting
ddx(sin2x+cosxsinx−cos2x)=(sinx−cos2x)(2sinxcosx−sinx)−(sin2x+cosx)(2sinxcosx+cosx)(sinx−cos2x)2
Simplifying
(2sin2xcosx−2sinxcos3x−sin2x+cos2xsinx)−(2sin3xcosx+2sinxcos2x+sin2xcosx+cos2x)(sinx−cos2x)2
(2sin2xcosx−2sinxcos3x−sin2x+cos2xsinx−2sin3xcosx−2sinxcos2x−sin2xcosx−cos2x)(sinx−cos2x)2
sin2xcosx−cos2xsinx−(sin2x+cos2x)−2sinx(cos2x+sin2x)(sinx−cos2x)2
Knowing that cos2x+sin2x=1=sin2x+cos2x
sin2xcosx−cos2xsinx−1−2sinx(1)(sinx−cos2x)2
sinxcosx(sinx−cosx)−1−2sinx(sinx−cos2x)2
sinxcosx(sinx−cosx)−(1+2sinx)(sinx−cos2x)2
Thus, the derivative of
sin2x+cosxsinx−cos2x is
sinxcosx(sinx−cosx)−(1+2sinx)(sinx−cos2x)2